Factors associating with differences in the incidence of renal replacement therapy among elderly: data from the ERA-EDTA Registry. Issue 8 (18th April 2018) - Helve, Jaakko; Kramer, Anneke; Abad-Diez, Jose M; Couchoud, Cecile; de Arriba, Gabriel; de Meester, Johan; Evans, Marie; Glaudet, Florence; Grönhagen-Riska, Carola; Heaf, James G; Lezaic, Visnja; Nordio, Maurizio; et al.
Abstract: Background: The incidence of renal replacement therapy (RRT) in the general population ≥75 years of age varies considerably between countries and regions in Europe. Our aim was to study characteristics and survival of elderly RRT patients and to find explanations for differences in RRT incidence. Methods: Patients ≥75 years of age at the onset of RRT in 2010–2013 from 29 national or regional registries providing data to the European Renal Association–European Dialysis and Transplant Association Registry were included. Chi-square and Mann–Whitney U tests were used to assess variation in patient characteristics and linear regression was used to study the association between RRT incidence and various factors. Kaplan–Meier curves and Cox regression were employed for survival analyses. Results: The mean annual incidence of RRT in the age group ≥75 years of age ranged from 157 to 924 per million age-related population. The median age at the start of RRT was higher and comorbidities were less common in areas with higher RRT incidence, but overall the association between patient characteristics and RRT incidence was weak. The unadjusted survival was lower in high-incidence areas due to an older age at onset of RRT, but the adjusted survival was similar [relative risk 1.00 (95% confidence interval, 0.97–1.03)] in patients from low- and high-incidence areas. Conclusions: Variation in the incidence of RRT among the elderly across European countries and regions is remarkable and could not be explained by the available data. However, the survival of patients in low- and high-incidence areas was remarkably similar.